2014
DOI: 10.1002/2014jd021595
|View full text |Cite
|
Sign up to set email alerts
|

The vertical distribution of black carbon in CMIP5 models: Comparison to observations and the importance of convective transport

Abstract: Citation:Allen, R. J., and W. Landuyt (2014), The vertical distribution of black carbon in CMIP5 models: Comparison to observations and the importance of convective transport, J. Geophys. Res. Atmos., 119, 4808-4835, doi:10.1002 Abstract Large uncertainty in the direct radiative forcing of black carbon (BC) exists, with published estimates ranging from 0.25 to 0.9 W m −2 . A significant source of this uncertainty relates to the vertical distribution of BC, particularly relative to cloud layers. We first compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 92 publications
3
68
3
Order By: Relevance
“…This bias appears to be more significant in NorESM and CESM, while CanAM produces particularly reasonable agreement with the observations, especially during the spring season. Comparisons of model results with aircraft measurements do not provide any evidence for large systematic overestimates of simulated BC concentrations in the upper troposphere in the Arctic in the AMAP models, which is different from conclusions in several previous studies [e.g., Koch et al ., ; Kipling et al ., ; Wang et al ., ; Allen and Landuyt , ; Samset et al ., ]. Furthermore, Eckhardt et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bias appears to be more significant in NorESM and CESM, while CanAM produces particularly reasonable agreement with the observations, especially during the spring season. Comparisons of model results with aircraft measurements do not provide any evidence for large systematic overestimates of simulated BC concentrations in the upper troposphere in the Arctic in the AMAP models, which is different from conclusions in several previous studies [e.g., Koch et al ., ; Kipling et al ., ; Wang et al ., ; Allen and Landuyt , ; Samset et al ., ]. Furthermore, Eckhardt et al .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, differences in upper tropospheric BC concentrations and burdens in simulations appear to be related to differences in simulated large‐scale lifting of air masses or convective transport of BC outside the Arctic. This is broadly consistent with Allen and Landuyt [] who found that Coupled Model Intercomparison Project Phase 5 climate models tend to produce higher concentrations of BC in the upper troposphere and lower stratosphere (UT/LS) than observed from aircraft. A modified version of one of the models in their study with reduced convective transport of BC produced lower concentrations and better agreement with observations in the UT/LS outside the Arctic.…”
Section: Resultsmentioning
confidence: 99%
“…Another modeling problem may be excessive convective transport and underestimation of the associated wet scavenging in convective clouds, which can lead to model overestimates of BC in the upper troposphere and lower stratosphere (Allen and Landuyt, 2014;Wang et al, 2014). Despite remaining difficulties, simulations of Arctic aerosols with many models have improved considerably in the last few years by updating the model treatment of some or all of the above-mentioned processes (Fisher et al, 2011;Breider et al, 2014;Sharma et al, 2013;Lund and Berntsen, 2012;Allen and Landuyt, 2014).…”
Section: S Eckhardt Et Al: Current Model Capabilities For Simulatinmentioning
confidence: 99%
“…In addition, in Fig. 5b-c, CCAM is within the range of estimates for total deposition, wet deposition fraction, burden, and lifetime of organic aerosols (OAs) and BC (Tsigaridis et al, 2014;Allen and Landuyt, 2014). CCAM modeled OC emissions and burden is converted to OA by multiplying by a factor of 1.4 for a consistent comparison (Tsigaridis et al, 2014).…”
Section: Southern African Aeronet Aod and α Ext Observationsmentioning
confidence: 59%